Update on the engineering design studies evaluated in the NRC report "Analysis of engineering design studies for demilitarization of assembled chemical weapons at Pueblo Chemical Depot." - Parker, Michael (National Academies Press, 2002)
Letter report containing several engineering design tests which had not been completed in time to be included in the earlier related report titled: Analysis of engineering design studies for demilitarization of assembled chemical weapons at Pueblo Chemical Depot.